Efisiensi Anggaran Berdasarkan Model Value For Money di Lembaga Pendidikan MA YPIA Cikeris - Moh Sugandi; Eka Mutia Sari Nur Hidayat; Muhammad Muthi Hamidi (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study examines budget efficiency in the monitoring and evaluation (M&E) process of educational institutions using the Value for Money (VfM) model. Effective budget management is essential for improving education quality, yet many schools still face challenges in monitoring, evaluation, and understanding the principles of economy, efficiency, and effectiveness. This study aims to analyze the implementation of the Value for Money model in school budget management and to examine the role of monitoring and evaluation in promoting efficient budget utilization. A qualitative phenomenological approach was employed through in-depth interviews with individuals involved in school budget management. The findings reveal that schools have applied the principles of Value for Money in practice, although most stakeholders are not formally familiar with the concept. The economic principle is reflected in budget allocation based on priority needs, while efficiency is demonstrated through the optimal use of available resources to support educational activities. Effectiveness is evident in budget utilization that contributes to improving learning quality. The study also found that monitoring and evaluation play an important role in ensuring budget accountability, although their implementation remains focused on administrative compliance rather than outcomes. Overall, adopting the Value for Money model can strengthen education budget management by promoting greater efficiency, effectiveness, transparency, and accountability